Level of public's acceptance towards COVID-19 vaccine / Ahmad Muzzammil Aqib Md Zin ... [et al.] - Md Zin, Ahmad Muzzammil Aqib; Md Noor, Nor Hasimah; Lokman, Nurul Akmal; Ridzuan, Abdul Rauf; Bakar, Mohd Hilmi (Faculty of Communication & Media Studies, 2021)
After almost 2 years since the first COVID-19 case outbreak, Malaysia had finally received the COVID-19 vaccines. There are several brands of vaccines from various manufacturers that had been tested and approved by National Pharmaceutical Regulatory Agency (NPRA). This study is conducted to identify the level of public's awareness and acceptance towards the COVID-19 vaccine. 44 online survey questions were prepared including questions related to demographic background. The Google Form survey was disseminated to family and friends via social media platform such as WhatsApp, Twitter and Instagram. A number of 405 respondents had answered the survey resulting to a positive result on the awareness (M = 3.60) and acceptance (M = 3.58) of public towards COVID-19 vaccine.